Effects of cultural diversity on individual establishments. Issue 1 (6th May 2014) - Brunow, Stephan; Blien, Uwe
Abstract : Purpose: – International immigration affects the degree of cultural diversity present in a labour force. The purpose of this paper is to focus on the consequences of immigration with respect to the level of cultural diversity by estimating employment functions for individual establishments. Design/methodology/approach: – The theory behind the empirical analyses is based on a "turned around" new economic geography model. The data basis used is a linked employer – employee data set generated by a fusion of the IAB Establishment Panel with the Employment Statistics of Germany, which provides very detailed information about individual workers and establishments. In the empirical part instrumental variables techniques are employed to solve the endogeneity issues involved. Findings: – In the empirical analyses it is shown that employment is lower when the degree of diversity is higher, regarding the revenue of an individual establishment as given. From this result it can be derived under the conditions of monopolistic competition (implying elastic product demand) that the establishment is able to occupy a relatively large part of the market. Finally, this implies relatively high labour demand. Practical implications: – The paper provides clear evidence that cultural diversity in single establishments enhance productivity. The question remains whether different employees interact each another or whether they are separated to different tasks within the establishment. In the latter case productivity gains are due to task-specific knowledge whereas in the former one the interaction of different cultures matters. This issue cannot be answered with the given data set. Originality/value: – Negative effects emerging from employing various cultures (such as language barriers) can be compensated. Thus, hiring foreign born workers does not mean a decline in productivity and a loss in competitiveness.